SAHD-10: development and initial validation of a short version of the Schedule of Attitudes Toward Hastened Death based on a large multinational sample - Kremeike, Kerstin; Boström, Kathleen; Dojan, Thomas; Montforte-Royo, Cristina; Rosenfeld, Barry; Voltz, Raymond; Rietz, Christian; Strupp, Julia (Palliative & supportive care, 2025)
ObjectivesWishes to hasten death (WTHDs) are common in patients with serious illness. The Schedule of Attitudes Toward Hastened Death (SAHD) is a validated 20-item instrument for measuring WTHD. Two short versions have also been developed based on statistical item selection. However, all existing versions show some limitations with potential for improvement. This study aims to develop and initially validate a theory-driven and statistically sound SAHD short version based on a large multinational sample to advance the WTHD assessment in different countries and with different legislations.MethodsA 3-step procedure was carried out including (1) theory-driven item selection, (2) exploratory, and (3) confirmatory factor analysis. We used a data set collected between 1998 and 2020 across 3 different countries (Germany, Spain, USA). Participants were N = 1156 complete cases (n = 181 German, n = 101 Spanish and n = 874 US) of severely ill adult in- and outpatients. They had to be ≥18 years and give informed consent.ResultsThe exploratory factor analysis revealed that 10 of 11 items previously selected theory-driven loaded on either of 2 factors: (1) WTHD and (2) internal locus of control. These factors showed good to excellent reliability according to Cronbach’s α and McDonald’s Ω, as well as an excellent fit of our data as an overall model for the total sample.Significance of resultsThe developed SAHD-10 represents a reliable and valid alternative to the SAHD and an efficient means to measure and further investigate a WTHD in cross-cultural clinical and research settings.
Gesehen am 23.05.2025